Sistem Pendukung Keputusan Pemilihan Televisi Bekas Terbaik Dengan Menggunakan Metode Multi Factor Evaluation Process (MFEP) - Syahrizal, Muhammad; Maulidza, Dwi (STMIK Budi Darma, 2018)
Various choices, be it type, model, or feature that will make you really a dilemma, so you are very afraid to make a decision. Therefore, some tips on buying goods in this case are the best used televisions, to anticipate that you can dare to make choices without being burdened by feeling confused. Decision Support System or SPK determining the selection of goods with the method (Multifactor Evaluation Process) produces a system that can determine an option that can help distributors in making decisions. SPK is an interactive system, which helps in making decisions through the use of data and models decisions to solve problems that are semi-structured or unstructured. The results of the study are first, to implement the best-used television decision support system decision using the multi factor evaluation process method so that the data can be very close to accurate. Second, provide the best solution in deciding the selection of the best used television for buyers or consumers.